Risk Assessment of Two Insecticides on Encarsia formosa, Parasitoid of Whitefly Bemisia tabaci - Zhan He; Yuan Liu; Lei Wang; Qiu Guo; Shaukat Ali; Xiao-Sheng Chen; Bao-Li Qiu (Insects, 2018)
The assessment of acute toxicity to insect natural enemies is very important for insecticide selection used within integrated pest management (IPM). The acute toxicity of abamectin and imidacloprid against Encarsia formosa, a parasitoid of Bemisia tabaci, was investigated. Abamectin had a high toxicity risk to E. formosa, while imidacloprid showed a medium toxicity risk. When treated with the lethal concentration 30 (LC30) of abamectin, the dwelling time of E. formosa in B. tabaci infested-plant-area (IPA) was significantly lower than in non-infested plant areas (non-IPA). In addition, the frequency of E. formosa entering into the two areas was not significantly different in the LC10 and LC30 treatments. Within the IPA, LC10, and LC30 treatments decreased the dwelling time and entering frequency of parasitoid significantly. For imidacloprid treatments, E. formosa stayed a longer time in the non-IPA than in the IPA when treated with LC30. The frequency of E. formosa entering into the two areas was only slightly different in the LC1, LC10, and LC30 treatments. Within the IPA, LC10 and LC30 treatments were significantly decreased in the dwelling time and the entering frequency of E. formosa. The results indicate that abamectin and imidacloprid have high or medium acute toxicity against E. formosa and a negative sublethal effect on its searching behaviour.